BmDaxx regulates apoptosis in cells and larval tissues of the silkworm (Bombyx mori) - JIAO Peng; XIAO Ying; LIU Zhen; CHEN Ruiting; LU Yan; XIN Huhu; MIAO Yungen (浙江大学学报. 农业与生命科学版, 2019)
We amplified and characterized the BmDaxx gene of the silkworm (Bombyx mori) by real-time quantitative polymerase chain reaction (RT-qPCR). The expression levels of BmDaxx and its downstream genes BmFadd and BmDredd showed significant increases after overexpression of BmDaxx. However, the expression levels of BmDaxx and BmFadd decreased significantly after siRNA interference of BmDaxx. Overexpression of BmDaxx increased the activity of the cystein-asparate protease-3/7 (caspase-3/7), while siRNA interference decreased the activity. When BmN cells were treated by caspase-3/7 inhibitor, the transcriptional levels of BmDaxx, BmFadd and BmDredd decreased as compared with controls. The expression level of BmDaxx was significantly higher in silk glands than in other organs at the silking stage, consistent with the silk gland degeneration at this stage. After injecting of the caspase inhibitor, the expression levels of the apoptosis-related genes BmDaxx, BmFadd and BmDredd showed significant decreases. It is concluded that there are direct relationships between BmDaxx and its predicted downstream genes BmFadd and BmDredd, which play critical roles both in BmN cells and in silk gland apoptosis.